Aprendizaje y divulgación científica de los sistemas de grabación y reproducción sonora a través de los cuentos. - Barbancho-Pérez, Ana María; Barbancho-Pérez, Isabel; Peinado-Domínguez, Alberto; Tardón-García, Lorenzo José (My University, 2024)
In this paper, the pilot experience of scientific dissemination based on the writing of stories by students of the ETSI Telecommunications, carried out in the academic year 2021-22, is presented. The aim of this experience is twofold: on the one hand, to learn how to popularize science to a children's audience and, at the same time, to work directly on the competence of transmitting information to a non-specialized audience (competence G-07). To evaluate the experience, questionnaires and interviews were carried out with both teachers and students involved in the activity. It was found that this experience has been very positive and has made it possible to work both on competence G-07 and on the writing of texts and scientific dissemination.
Keywords: Divulgación científica; Cuentos infantiles; Pedagogía; Aprendizaje; Divulgacion